The new digital era governance how new digital technologies are shaping public governance - Tan, Evrim; Crompvoets, Joep (Wageningen Academic Publishers, 2022)
"Data-driven new digital technologies can partially or fully replace the human agency in policymaking and governance. So far, the impact of these technologies on the human agency in public governance and the role of public servants has not been explored fully. The 'New Digital Era Governance' aims to fill this gap by bringing together expertise from public management, public policy, digital governance, information management, and ICT law. A central topic in the book is to explore how public administration can implement big data solutions in public governance processes that use the full potential of data processing technologies, such as AI and blockchain technologies, without undermining the role of human agency in decision-making processes and the legitimacy of democratic and regulatory institutions. The readers will find practical guidelines and insight on how to implement these new technologies into public service processes by drawing on the empirical findings from the Belgian case."--Page 4 of cover
Keywords: E-Government; Belgien; Public administration / Technological innovations / Belgium; Public administration / Belgium / Data processing